Critical infrastructure in the railway transport system - Fuchs, Pavel; Soušek, Radovan; Šustr, Martin; Rozová, Dana; Šohajek, Petr (International Institute of Informatics and Systemics, 2018)
The critical infrastructure in the railway transport is very dynamic system. In the last years are created new critical infrastructure elements. The new critical infrastructure element must be protected, like origin, as well. The most critical infrastructure elements are related to the IT development. The new systems haven’t sufficient resilience. This article describes the new crisis infrastructure elements in the railway transport. This article suggests ways to improve resilience, too.
Kritická infrastruktura v železničním dopravním systému
Keywords: railways; crisis infrastructure; resiliance; železnice; kritická infrastruktura; odolnost